Multispectral tunable symmetry-protected bound states in the continuum in all-dielectric split-ring resonator metasurfaces. (2nd February 2023) - Sharma, Shubhanshi; Lahiri, Basudev; Varshney, Shailendra
Abstract: Symmetry incompatible bound states in the continuum (BICs) are the non-radiating states that remain decoupled from the radiation continuum due to the symmetry mismatch. However, it has always been challenging to observe multiple symmetry-protected BICs in single resonator dielectric metasurfaces. This work reports multiple symmetry-protected BICs for both linear polarizations in all-dielectric metasurfaces made up of split-ring resonators (SRRs). Intensive numerical simulations predict that SRR can support a high-quality factor ( Q ) of 10 6 for standalone and with substrate in presence of asymmetry. However, for a realistic and practical scenario, a Q -factor of ≈ 8000 for standalone structures is achieved, which reduces by a factor of 1.25 in the presence of silica substrate. Even if the out-of-plane asymmetry is introduced either in the geometry or variation in the angle of incidence, BICs are transformed into quasi-BICs possessing Fano resonance. Eigenmode and multipole decomposition analysis confirm multiple BIC resonances; notable dominant contributions are from magnetic dipole, toroidal dipole, and electric and magnetic quadrupoles. Integrating monolayer graphene adds tunability to the metasurface, where distinct quasi-BIC modes can be employed to facilitate an excellent switching.